Núcleos de población en riesgo de inundación fluvial en Aragón: diagnóstico y evaluación para la ordenación del territorio - Doménech Zueco, Sergio; Ollero Ojeda, Alfredo; Sánchez Fabre, Miguel (Geographicalia, 2015)
This paper gathers an inventory of population settlements that are in situation of risk by fluvial floods in Aragón. The diagnosis of these nucleus has been made by means of photo-interpretation. The cases of study have been catalogued based on the type of fluvial course that crosses them and the density of settlement that can be affected by the floods. The information has been analyzed according to provinces, by the kind of fluvial course and by the density of constructions. The assessment of the population settlements has been completed with the existence of past floods, the interventions in rivers that minimizes the hazard probability and their inclusion in the Flood Special Plan in Aragón made by Civil Protection. This assessment can be useful for landmanagement at regional scale, and for this reason lines of action for the future are set out.
Keywords: Natural hazards; river floods; population settlements; land management; Aragón.